Esters of Bendamustine Are by Far More Potent Cytotoxic Agents than the Parent Compound against Human Sarcoma and Carcinoma Cells - Huber, Stefan; Huettner, Johannes Philip; Hacker, Kristina; Bernhardt, Günther; König, Jörg; Buschauer, Armin (PLOS ONE, 2015)
The alkylating agent bendamustine is approved for the treatment of hematopoietic malignancies such as non-Hodgkin lymphoma, chronic lymphocytic leukemia and multiple myeloma. As preliminary data on recently disclosed bendamustine esters suggested increased cytotoxicity, we investigated representative derivatives in more detail. Especially basic esters, which are positively charged under physiological conditions, were in the crystal violet and the MTT assay up to approximately 100 times more effective than bendamustine, paralleled by a higher fraction of early apoptotic cancer cells and increased expression of p53. Analytical studies performed with bendamustine and representative esters revealed pronounced cellular accumulation of the derivatives compared to the parent compound. In particular, the pyrrolidinoethyl ester showed a high enrichment in tumor cells and inhibition of OCT1- and OCT3-mediated transport processes, suggesting organic cation transporters to be involved. However, this hypothesis was not supported by the differential expression of OCT1 (SLC22A1) and OCT3 (SLC22A3), comparing a panel of human cancer cells. Bendamustine esters proved to be considerably more potent cytotoxic agents than the parent compound against a broad panel of human cancer cell types, including hematologic and solid malignancies (e.g. malignant melanoma, colorectal carcinoma and lung cancer), which are resistant to bendamustine. Interestingly, spontaneously immortalized human keratinocytes, as a model of “normal” cells, were by far less sensitive than tumor cells against the most potent bendamustine esters.